Spontaneous emphysematous osteomyelitis of the spine: A case report - Di Stasi, Martina (Radiol Case Rep, 2020)
Spontaneous emphysematous osteomyelitis of the spine is a very rare but severe condition caused by gas-forming microorganisms. We present the case of a 41-year-old obese male patient presenting at the Emergency Department with diabetic ketoacidosis, fever, and difficulty in walking. computed tomography and magnetic resonance imaging of the spine revealed bone marrow edema and intraosseous gas collections at the level of the fourth and fifth lumbar metameres, suggesting an osteomyelitis sustained by gas-forming microorganisms, which was then confirmed by the isolation of Klebsiella pneumonia in blood culture. Imaging plays a central role for the diagnosis of emphysematous osteomyelitis: the presence of multiple intraosseous gas collections of variable size, especially in patients with specific risk factors, is highly suggestive of an infection caused by gas-forming pathogens. Being familiar with this peculiar neuroradiological appearance is essential to ensure an early diagnosis and a timely antimicrobial therapy, which can considerably ameliorate the prognosis.